Safety and Antiviral Activity of EGFR Inhibition by Erlotinib in Chronic Hepatitis C Patients: A Phase Ib Randomized Controlled Trial. Issue 6 (1st June 2022) - Saviano, Antonio; Habersetzer, François; Lupberger, Joachim; Simo-Noumbissie, Pauline; Schuster, Catherine; Doffoël, Michel; Schmidt-Mutter, Catherine; Baumert, Thomas F.
Abstract : INTRODUCTION: Significant hepatocellular carcinoma (HCC) risk persists after chronic hepatitis C (CHC) cure. Preclinical studies have shown that erlotinib, an oral epidermal growth factor receptor (EGFR) inhibitor, has an antiviral activity and HCC chemopreventive effect. Erlotinib is metabolized in the liver, and its safety in patients with CHC is unknown. This study aimed to assess the safety and antiviral activity of erlotinib in patients with CHC. METHODS: In this investigator-initiated dose-escalation phase Ib prospective randomized double-blind placebo-controlled study, noncirrhotic hepatitis C virus (HCV) patients received placebo or erlotinib (50 or 100 mg/d) for 14 days with a placebo-erlotinib ratio of 1:3. Primary end points were safety and viral load reduction at the end of treatment (EOT). The secondary end point was viral load reduction 14 days after EOT. RESULTS: This study analyzed data of 3 patients receiving placebo, 3 patients receiving erlotinib 50 mg/d, and 3 patients receiving erlotinib 100 mg/d. One grade 3 adverse event was reported in the placebo group (liver enzymes elevation), leading to treatment discontinuation and patient replacement, and 1 in the erlotinib 100 mg/d group (pericarditis), which was not considered to be treatment-related. Grade 2 skin rash was observed in 1 erlotinib 100 mg/d patient. No significant HCV-RNA level reduction was noted during treatment, but 2 of the 3 patients in the erlotinib 100 mg/d group showed a decrease of >0.5 log HCV-RNA 14 days after EOT. DISCUSSION: Erlotinib demonstrated to be safe in noncirrhotic CHC patients. An antiviral activity at 100 mg/d confirms a functional role of EGFR as an HCV host factor in patients. These results provide perspectives to further study erlotinib as an HCC chemopreventive agent in patients with CHC.